Investigation of Construct Validity of The Indonesian Version of The Financial Wellness Questionnaire - Renanita, Theda; Hidayat, Rahmat; Santoso, Agung (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2024)
Developing a financial wellness questionnaire in Indonesia is necessary to evaluate household financial situation. However, there has been a scarcity of research that adapts and tests the psychometric properties of the financial wellness questionnaire in Indonesia. The purpose of the current study was to evaluate the psychometric properties of the Indonesian version of Joo’s Financial Wellness Questionnaire. Data was collected using an online survey consisting of 388 participants (25-60 years). The results provided two evidences of the validity of the Indonesian version of the Financial Wellness Questionnaire based on the scale’s internal structure. Firstly, the structure of relationships between items in the questionnaire fits the theoretical model of financial wellness, which includes objective and subjective measurements. Furthermore, the structure of relationships between items in the subjective measure fits the theoretical model of the subjective measure of financial wellness, which comprises aspects of subjective perception, financial behavior, and financial satisfaction. Based on the evaluation of the Multiple Indicator Multiple Cause (MIMIC) model fitted, we also identified the effects of gender, education, and socio-economic status (SES) on some of the subjective financial wellness indicators. Therefore, the questionnaire should consider the aforementioned variables in interpreting the questionnaire scores.